INTRAOCULAR ELECTROCHEMICAL LYSIS TECHNIQUE AT THE STAGE OF LARGE CHOROIDAL MELANOMA ENDORESECTION - Y. A. Belyi; A. V. Tereshchenko; A. V. Shatskikh; D. K. Solovyov (Офтальмохирургия, 2015)
Purpose. A case report of intraocular electrochemical lysis (ECL) technique at the stage of endoresection for large choroidal melanoma. Material and methods. Endoresection with the intraoperative intraocular ECL was performed in one patient (1 eye) with a large T2N0M0 choroidal melanoma (tumor thickness: 10mm, base diameter: 13.7x15.4mm, juxtapapillary localization). An original method of a combined positioning of two platinum electrodes (extrascleral anode and intraocular cathode) was used for the ECL during endoresection. The removed material was examined morphologically.Results. The tumor was removed completely without complications. The anatomical retinal reattachment was achieved. Morphological examinations testified an ECL efficacy for both tumor and tumor cells destruction. Material removed during endoresection corresponded to tumor fragments in pathomorphism. Extensive fields of various necrosis types were detected, such as: acellular detritus with tumor parenchyma complete destruction, tumor parenchyma lixiviation; coagulation necrosis with destroyed parenchyma and compacted tumor stroma. An absence of viable tumor cells and tumor fragmentation did not allow to verify its histological tumor structure.Conclusions. New vitreoretinal technologies and new intraocular methods that destroyed tumor tissue could make the endoresection a promising and reassuring organ-safe treatment mode.